PENGARUH ABSORSI GAS CO2 DAN H2S DALAM BIOGAS MENGGUNAKAN PASTA BATU APUNG TERHADAP PENINGKATAN UNJUK KERJA MOTOR BAKAR - Sutanto, Rudy; Alit, Ida Bagus; Rezeki, Gilang (Universitas Mataram, 2016)
Human dependence on fossil fuels cause the reserves of energy resources is increasingly reduced. To overcome these problems is urgently needed alternative fuels which are cheap and readily available, one alternative fuel is biogas. However, the use of biogas not yet maximized because of low heating value of the biogas produced from the process without purification. Premium fueled vehicle proved to be turned on using biogas. Tests conducted on the variation of the engine rotation of 1500, 2500, 3500, and 4500 rpm and variations of biogas that has been purified using the paste pumice stone with a variation of the flow rate of purification of 2 liters / minute, 6 liter / minute, and 10 liters / minute. In this test should be able to get the best performance in terms of fineness engine rotation (force braking and fuel consumption). From the test results with the variation of rotation and flow rate variations purification of biogas obtained performance of the motor fuel of the best on rotation 4500 rpm with a flow rate of fuel biogas purification of 2 liters / minute produces a torque value of 6.98 Nm and an effective power of 3288.09 Watt while the value SFCE by 0.33 Liter / Jam.Watt. This proves that, biogas purification using paste pumice stone is able to improve quality of biogas.